Long-Term Response of Pembrolizumab in a Patient with Metastatic Squamous Non-Small Cell Lung Cancer on Hemodialysis: Case Report and Review of the Literature - Jae Won Yun; Jung Kwon; Taekyu Lim (Medicina, 2023)
In patients with renal failure and hemodialysis, there are difficulties in drug selection and dose adjustment for cancer treatment. The use of immune checkpoint inhibitors (ICIs), including pembrolizumab, approved by the U.S. Food and Drug Administration (FDA) for patients with metastatic non-small cell lung cancer (NSCLC) in 2015, has become an important option for the treatment of metastatic NSCLC. However, data regarding the dosage and schedule for long-term use of ICIs, especially pembrolizumab, in hemodialysis patients are limited. We present the case of a patient with metastatic squamous NSCLC who demonstrated a long-term partial response to pembrolizumab monotherapy for 45 months during hemodialysis and showed no immune-related adverse events (irAEs). To our knowledge, this is the longest remission to be reported without irAEs after discontinuation of pembrolizumab in a NSCLC patient undergoing HD. In addition, we reviewed previously reported lung cancer patients who used ICI during dialysis, comparing them with our case in clinical aspect. We believe that this report will provide clinical insights into the long-term efficacy and safety of pembrolizumab in lung cancer patients undergoing hemodialysis.